Well-ordered and non-well-ordered lower and upper solutions for periodic 2N-dimensional systems - Klun, Giuliano; Sfecci, Andrea (Topological Methods in Nonlinear Analysis, 2025)
In this paper we consider a class of periodic problems associated with 2N-dimensional systems of differential equations. Our aim is to generalize the theory of lower and upper solutions following the way paved in previous works. After a careful analysis of the dynamics in the phase space, the proofs take advantage of topological degree arguments.